The death of ivan ilyich eaudiobook - Tolstoy, Leo (Recorded Books Inc., 2014)
Leo Tolstoy is quite simply one of the greatest writers to ever set pen to paper. Immortalized by such epic novels as War and Peace and Anna Karenina, Tolstoy's genius was also readily apparent in his short fiction. The Death of Ivan Ilych follows the career of the unremarkable title character, who does not question his desire to live an "easy, agreeable, gay and always decorous" life until he is lying on his death bed.